Comparing Federal Indigenous Health Policy Reform in Canada and the United States: The Shift to Indigenous Self-Determination in Health Care - Denise Webb; Angela Mashford-Pringle; Sara Allin; Dane Mauer-Vakil (McMaster University Library Press, 2022)
Federal governments in Canada and the United States have followed similar timelines and events in their efforts to support Indigenous self-determination in health care. Since colonization, both settler colonies have aimed to assimilate Indigenous Peoples into settler society, in disregard of inherent Indigenous self-determining rights and titles. By the 1970s their policy agendas shifted towards Indigenous self-determination, including in matters of health service planning and delivery at the community-level. This paper analyzes this shift in policy from a comparative perspective with the aim of informing future reforms. We identify and examine the policy instruments used in the process, finding a greater use of regulatory instruments in the United States, compared to informative tools in Canada. We also discuss the associated impacts of the reform on the ability to practice self-determining activities within communities, highlighting some of the administrative enablers and barriers within and around health care settings. As little research has compared health policy reforms related to matters of Indigenous health in Canada and the United States, this paper provides new insights into the drivers and nature of the policy shift toward self-determination at the federal level and suggests grounds for further investigation.